(untitled) (Research, Society and Development, 2024)
This article investigates the methodologies used in teaching Human Anatomy and Physiology in Youth and Adult Education (EJA) in Brazil, focusing on pedagogical practices that promote student retention and academic success. Given the high dropout rates and diverse student backgrounds, EJA requires differentiated methodologies that respect the experiences and realities of its students. This article aims to analyze, using an integrative review, the teaching methodologies of Human Anatomy and Physiology at EJA used between 2012 and 2022. Pedagogical practices and teacher training in this area were examined, identifying a scarcity of studies specifically addressing the teaching of Biological Sciences in EJA, particularly in Anatomy and Physiology. Results indicate that teaching these subjects in EJA remains superficial due to a lack of active and contextualized methodologies, suggesting an important theoretical area to explore. This area integrates teacher training, skill development, and methodological innovations to promote a pedagogical approach that goes beyond technicism and meets the specific needs of EJA students.